2002
DOI: 10.1002/mds.10242
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the non‐rapid eye movement sleep electroencephalogram in patients with newly diagnosed Parkinson's disease: Effects of dopaminergic treatment

Abstract: We investigated non-rapid eye movement (non-REM) sleep in patients with newly diagnosed Parkinson's disease (PD) who had never previously received dopaminergic medication. There were no significant differences in the conventional sleep parameters between de novo patients with PD and a healthy control group, but the length of stage 1 sleep and the number of awakenings increased significantly upon administration of dopaminergic drugs. Analyzing the quantitative electroencephalogram (EEG), we observed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 28 publications
9
77
1
2
Order By: Relevance
“…With cabergoline therapy, we found a trend towards increased stage 1 and stage 2 sleep. However, epoch assignment to conventional Rechtschaffen and Kales sleep stages has a limited reliability in PD (Bliwise et al, 2000), a drawback, that can possibly be resolved by more sophisticated forms of analyses (Brunner et al, 2002). When non-REM sleep stages one to four were summed up as has been proposed for PD (Bliwise et al, 2000), there was still no difference in the amount before and during cabergoline therapy.…”
Section: Discussionmentioning
confidence: 99%
“…With cabergoline therapy, we found a trend towards increased stage 1 and stage 2 sleep. However, epoch assignment to conventional Rechtschaffen and Kales sleep stages has a limited reliability in PD (Bliwise et al, 2000), a drawback, that can possibly be resolved by more sophisticated forms of analyses (Brunner et al, 2002). When non-REM sleep stages one to four were summed up as has been proposed for PD (Bliwise et al, 2000), there was still no difference in the amount before and during cabergoline therapy.…”
Section: Discussionmentioning
confidence: 99%
“…77 Dopamine agonists increase the duration of stage I sleep and increase the number of awakenings. 78 Low-dose dopamine agonists have been associated with insomnia, whereas higher doses can cause EDS. 58 Selegiline can cause sleep initiation insomnia attributed to the stimulating effect of its amphetamine metabolite.…”
Section: Disorders Of Sleep Initiation and Maintenancementioning
confidence: 99%
“…In agreement with the reported subjective sleep disturbances, previous polysomnographic studies showed that patients with Parkinson's disease exhibit significant abnormalities in sleep architecture not only in fully developed motor Parkinson's disease [12] but in the early phase of the disease as well. These abnormalities include increased sleep latency, reduced sleep efficiency, reduced rapid eye movement (REM) sleep [7], and significant changes in the REM and non-REM sleep architecture [13][14][15][16].…”
Section: Subjective Sleep Disturbances/ Insomniamentioning
confidence: 99%